Criminal identities and consumer culture crime, exclusion and the new culture of narcissism - Hall, Steve; Winlow, Simon (Willan, 2008)
Using unique data taken from criminals locked in lower class locations, this book aims to uncover feelings and attitudes towards a variety of criminal activities.
Includes bibliographical references (p. 223-235) and indexes
Keywords: Criminal psychology; Criminals / Great Britain / Attitudes; Poor / Great Britain / Attitudes; Criminels - Grande-Bretagne - Attitudes; Pauvres - Grande-Bretagne - Attitudes; Psychologie criminelle; Criminals -- Great Britain -- Attitudes; Poor -- Great Britain -- Attitudes; Konsumgesellschaft; Kriminalpsychologie; Großbritannien